ANALISIS PEMASARAN TBS (TANDAN BUAH SEGAR) KELAPA SAWIT PEKEBUN SWADAYA DI KOPERASI SAWIT JAYA KAMPUNG BENTENG HULU KECAMATAN MEMPURA KABUPATEN SIAK - Fadilah Fadilah; Novia Dewi; Sakti Hutabarat (Indonesian Journal of Agricultural Economics, 2018)
Palm oil marketing in Fresh Fruit Bunch (FFB) form is often become a problem faced byindependent farmers. Independent farmers often used marketing organization to offer their FFBto palm oil factory. The marketing organization such as KUD (Koperasi Unit Desa), collectingtraders/middlemen, and wholesalers. The existency of marketing organization causing higher costof marketing and higher marketing margin. In this condition, independent farmers suffer the mostfinancial loss. The aims of this study were (1) identification and analysis of FFB marketingchannel for independent farmers (2) analysis of marketing margin, farmer share, and marketingefficiency. Population in this study was independent farmers in Sawit Jaya Corporation. Theresult of this study showed that the marketing channels of independent farmers consist of threechannels: marketing channel I from farmers, KUD (Koperasi Unit Desa), and wholesalers,marketing channel II from farmers, collecting traders, and wholesalers, and marketing channel IIIfrom farmers directly to wholesalers. Channel III has the lowest margin value of IDR 200/kg.Channel III is more efficient than channel I and channel II. Channel III has an efficiency value of8,82% with a total marketing cost of IDR 150/kg and only involves wholesalers in its marketingchannel. Farmer’s share in marketing channel I is 86,18%, marketing channel II 79,41% andmarketing channel III 88,24%.